2012
DOI: 10.2355/isijinternational.52.1879
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Intergranular Corrosion of AISI 304 Stainless Steel and Chrome-Manganese Austenitic Stainless Steel

Abstract: The use of Chrome-Manganese austenitic stainless steel (Cr-Mn ASS) has tremendously increased in past few years in applications like home accessories, office appliances, light poles, etc and it is serving as an alternative to 300 series. But, the study related to sensitization behavior of these steels is scanty. Therefore, this paper aims a systematic comparison on intergranular corrosion of AISI 304 stainless steel and Cr-Mn ASS. The qualitative and quantitative comparison of degree of sensitization of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The results in Table 1 indicate that the classifications of the structures and DoS fall within the aforementioned ranges, i.e., the DoS of the structure classified as step was Behavior of DoS as a function of sensitization time at 600, 800 and 900 °C 0.001, that of the dual structure ranged from 0.040 to 0.051, and that of the ditch structure varied from 0.055 to 0.570. A comparison of these values with data reported in the literature obtained under similar heat treatment conditions and with DL-EPR tests indicated that the values of this study were relatively higher, possibly because the carbon content of the steel used here was about twice as high 2,26,27 . In Figure 3, note that the DoS decreased in the range of 600-900 °C in response to increasing temperature.…”
Section: Resultssupporting
confidence: 73%
“…The results in Table 1 indicate that the classifications of the structures and DoS fall within the aforementioned ranges, i.e., the DoS of the structure classified as step was Behavior of DoS as a function of sensitization time at 600, 800 and 900 °C 0.001, that of the dual structure ranged from 0.040 to 0.051, and that of the ditch structure varied from 0.055 to 0.570. A comparison of these values with data reported in the literature obtained under similar heat treatment conditions and with DL-EPR tests indicated that the values of this study were relatively higher, possibly because the carbon content of the steel used here was about twice as high 2,26,27 . In Figure 3, note that the DoS decreased in the range of 600-900 °C in response to increasing temperature.…”
Section: Resultssupporting
confidence: 73%
“…Microstructures with partially ditched grain boundaries represent dual structures while one or more grains completely surrounded by ditches are called as ditch structures. 11,17,24,25) Degree of sensitization (DOS) was obtained using DLEPR test. Solution containing of 0.5 M H2SO4 + 0.01 M NH4SCN (at room temperature, 27°C) was used to perform DLEPR test.…”
Section: Methodsmentioning
confidence: 99%
“…In sensitization phenomena, the steel is subjected to slow heating or cooling in the temperature range of 723-1 123 K [14][15][16] which extracts chromium from the grains and forms chromium carbide (Cr23C6) at grain boundaries, leaving a Cr-depleted zone extending adjacent to either side of grain boundaries. Taiwade et al 17) recently published electrochemical data on sensitization behaviour of Cr-Mn ASS. They also compared IGC behaviour and corrosion resistance of Cr-Mn steel with AISI 304 SS systematically.…”
Section: Introductionmentioning
confidence: 99%
“…6, in the ASTM A262 Practice E test, micro cracks in micro fissure form were observed in the bent areas on which the bending test was conducted. It is known that the formation of these micro fissures is due to the ditch structure caused by intergranular corrosion 11) . For analyzing the causes of forming the ditch structure and micro cracks in the form of micro fissures observed in the ASTM A262 practice test, TEM analysis was performed as shown in Fig.…”
Section: Effect Evaluation Of Solution Heat Treatment Holding Timementioning
confidence: 99%